Lessons in Gratitude - Dworkin, Aaron P (University of Michigan Press, 2024)
Lessons in Gratitude tells the story of Aaron Dworkin, a MacArthur Fellow, social entrepreneur, and spoken word artist who has dedicated his life’s work to changing the face of classical arts in the world. The themes of persistence, passion, and loyalty shine through stories of an unhappy childhood, a lifelong search for identity, and the obstacles of race, culture, and class. Readers will learn how the author greets these challenges and how they drove him to make a difference for people who are shut out of opportunity. Persistence in the face of multiple failures and false starts ultimately led Dworkin to create the Sphinx Organization, whose mission is to address the underrepresentation of Black and Latinx people in the field of the classical arts.